Robustness of radiation beam profile measurements - Nykänen, Topi (2023)
In this master’s thesis, profile measurements of PTW Semiflex 3D and PTW Semiflex ionisation chambers in addition to IBA MatriXX matrix detector were compared to each other using different measurement set-ups. The ionisation chamber measure- ments were done in a water phantom in horizontal and vertical orientations. Using two different set-ups in the horizontal orientation. The first horizontal set-up used the current clinical quality assurance program in Tampere University Hospital with the wire of the chamber lying deep in the water phantom. The second horizontal measurements were done with more of the wire in the radiation field by having the wire closer to the surface of the water. Measurements were done with 6, 10 and 15 MV photon fields. Flattened fields were measured with 6 and 15 MV energies. Flattening filter free fields were measured for the 6 and 10 MV fields. Field size was set to 20x20 cm². All of the measurements were repeated with adding 5° wedge in the radiation beam.